2006
DOI: 10.1159/000093904
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Significance of a Longer Duration of Neoadjuvant Hormonal Therapy prior to Radical Prostatectomy for High-Risk Prostate Cancer in Japanese Men

Abstract: Introduction: The objective of this study was to evaluate the therapeutic significance of a longer duration of neoadjuvant hormonal therapy (NHT) followed by radical prostatectomy (RP) in Japanese men with high-risk prostate cancer. Materials and Methods: This study included a total of 42 patients with high-risk prostate cancer who were treated with NHT for ≧8 months prior to RP. In this series high-risk prostate cancer was defined as clinical stage T2c or T3, pretreatment serum prostate-specific antigen (PSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A study has shown that the 5‐year recurrence‐free progression probabilities for lower‐grade PCa (63–96%) and high‐grade PCa (26–48%) have great differences . Lower‐grade PCa patients may benefit from relatively conservative treatment strategies or short‐time neoadjuvant antiandrogen therapy (ADT) for 4–6 months, while high‐grade PCa patients are suggested a longer ADT with 2–3 years that may improve the prognosis and reduce mortality . However, GS can only be determined via needle biopsy or resection .…”
mentioning
confidence: 99%
“…A study has shown that the 5‐year recurrence‐free progression probabilities for lower‐grade PCa (63–96%) and high‐grade PCa (26–48%) have great differences . Lower‐grade PCa patients may benefit from relatively conservative treatment strategies or short‐time neoadjuvant antiandrogen therapy (ADT) for 4–6 months, while high‐grade PCa patients are suggested a longer ADT with 2–3 years that may improve the prognosis and reduce mortality . However, GS can only be determined via needle biopsy or resection .…”
mentioning
confidence: 99%